The Correlation of Learning Motivation and Learning Environment with Pancasila and Civic Education’s Learning Outcomes of Grade V Students - Erna Hendrawati; Wuri Wuryandani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Learning motivation and learning environment have an important influence on student learning success. This study aims to analyze the correlation between learning motivation and learning environment with the learning outcomes of Pancasila and Civic Education (PPKn) learning outcomes of Grade 5 students partially and simultaneously. The research population was 287 students, the sample was taken using the simple random technique with the Slovin formula resulting in 165 students as sample. This study used a quantitative approach. Data was collected by questionnaires and documentation techniques. The validity of the items was obtained from the product moment correlation. Furthermore, the reliability of the items was obtained by using alpha formula. Simple linear regression analysis and multiple regression analysis were used to analyzed the data after the researchers conducted prerequisite analysis tests including normality tests, multicollinearity tests, and linearity tests . The results of this study shows (1) there is a significant positive correlation between learning motivation and Pancasila and Civic Education’s learning outcomes; (2) there is a significant positive correlation between the learning environment and Pancasila and Civic Education learning outcomes; (3) there is a significant positive correlation between learning motivation and learning environment with Pancasila and Civic Education of Grade V elementary school’s students.